Review of Ban Chiang, Northeast Thailand, Volume 2 (2A, 2B, 2C, 2D) - Thanik Lertchanrit (SPAFA Journal, 2024)
White, Joyce C. and Elizabeth G. Hamilton (editors). 2018. Ban Chiang, Northeast Thailand, Volume 2A: Background to the Study of the Metal Remains. University of Pennsylvania Museum of Archae¬ology and Anthropology, Philadelphia. 265 pages.